Report on Workshop "Marine Science Program in the 44th Japanese Antarctic Research Expedition on a Charter Research Vessel" - Tsuneo Odate; Sakae Kudoh; Shuki Ushio; Atsushi Tanimura; Toru Hirawake; Mitsuo Fukuchi (National Institute of Polar Research, 2003)
A workshop on "Marine Science Program in the 44th Japanese Antarctic Research Expedition on a Charter Research Vessel" was held on 15th October 2002 at the convention hall of the National Institute of Polar Research with 34 participants. Most of the participants will join the research cruise organized by the 44th Japanese Antarctic Research Expedition (JARE-44) using a charter vessel. One of the purposes of this workshop is to give detailed information on the JARE system. At the same time, safety guidelines for the cruise were explained. In addition, the work schedule for the cruise was revised based on detailed requests from the participants.